An Analysis of Students Motivation in Online Learning Based on Realistic Mathematical Comic Videos - Tetty Natalia Sipayung; Sinta Dameria Simanjuntak; Ariyadi Wijaya; Sugiman Sugiman (Budapest International Research and Critics University, 2020)
In this era of revolution 4.0, it is hoped that everyone will be active in managing their knowledge through digital media. Digital media needs to be well designed attractive. This can have an impact on motivation and learning outcomes, especially in the field of education. In online learning, digital media is an alternative in helping the learning process. Therefore a qualitative research was conducted. The subjects of this study were seventh grade students of SMP HKBP Lubuk Pakam for the 2020/2021 Academic Year who applied online learning assisted by realistic mathematics comic videos. While the object of this study is learning motivation so that the purpose of this study to analyze the learning motivation of these students. Based on the results of the provision of a learning motivation questionnaire, it was found that the average learning motivation of students who were taught using realistic mathematics comic videos in online learning was high which was assessed based on six indicators, namely responsibility, trying to excel, liking challenges, independence, fortitude, and resilience. This is a positive attitude that supports efforts to improve learning outcomes, especially in online learning.